Multibacillary leprosy by population groups in Brazil: Lessons from an observational study. - Mauricio Lisboa Nobre; Ximena Illarramendi; Kathryn Margaret Dupnik; Mariana de Andrea Hacker; José Augusto da Costa Nery; Selma Maria Bezerra Jerônimo; Euzenir Nunes Sarno (Public Library of Science (PLoS), 2017)
BACKGROUND:Leprosy remains an important public health problem in Brazil where 28,761 new cases were diagnosed in 2015, the second highest number of new cases detected globally. The disease is caused by Mycobacterium leprae, a pathogen spread by patients with multibacillary (MB) leprosy. This study was designed to identify population groups most at risk for MB disease in Brazil, contributing to new ideas for early diagnosis and leprosy control. METHODS:A national databank of cases reported in Brazil (2001-2013) was used to evaluate epidemiological characteristics of MB leprosy. Additionally, the databank of a leprosy reference center was used to determine factors associated with higher bacillary loads. RESULTS:A total of 541,090 cases were analyzed. New case detection rates (NCDRs) increased with age, especially for men with MB leprosy, reaching 44.8 new cases/100,000 population in 65-69 year olds. Males and subjects older than 59 years had twice the odds of MB leprosy than females and younger cases (OR = 2.36, CI95% = 2.33-2.38; OR = 1.99, CI95% = 1.96-2.02, respectively). Bacillary load was higher in male and in patients aged 20-39 and 40-59 years compared to females and other age groups. From 2003 to 2013, there was a progressive reduction in annual NCDRs and an increase in the percentage of MB cases and of elderly patients in Brazil. These data suggest reduction of leprosy transmission in the country. CONCLUSION:Public health policies for leprosy control in endemic areas in Brazil should include activities especially addressed to men and to the elderly in order to further reduce M. leprae transmission.